UV/chlorine and chlorination of effluent organic matter fractions: Tracing nitrogenous DBPs using FT-ICR mass spectrometry. (1st March 2023) - Wang, Yuru; Xiang, Yingying; Marques dos Santos, Mauricius; Wei, Gaoling; Jiang, Bin; Snyder, Shane; Shang, Chii; Croué, Jean-Philippe
Highlights: UV/Cl2 generated more diverse N-DBPs with higher intensity than chlorination. UV/Cl2 led to more hydrophilic, less aromatic, higher Cl-incorporating DBPs than chlorination. TPI EfOM formed more specific N-DBPs than HPO fraction by both UV/Cl2 and chlorination. DBPs with significant rank correlation with cell DNA damage were identified. UV/Cl2 reduced the cytotoxicity but enhanced oxidative stress-induced DNA damage. Abstract: UV/chlorine process is a promising advanced treatment to eliminate pathogen and remove refractory micropollutants for reclamation of municipal secondary effluent. However, effluent organic matter (EfOM) featuring high organic nitrogen content serves as a potential precursor for nitrogenous disinfection byproducts (N-DBPs) of health concern. The molecular-level alteration of a hydrophobic (HPO) EfOM fraction and a transphilic (TPI) EfOM fraction isolated from the same municipal effluent and the formation of N-DBPs in the UV/chlorine were tracked by ultrahigh-resolution mass spectrometry. Compared with chlorination, UV/chlorine induced a significantly greater modification on the molecular composition of EfOM and resulted in formation of unique formulae and chlorinated molecules with higher degree of oxidation, lower aromaticity, and less carbon number due to the involvement of reactive radical species. For both EfOM fractions, UV/chlorine formed more diverse DBPs with higher intensity and Cl-incorporation than chlorination. The TPI fraction of EfOM characterized by higher O/C and N/C ratios generated more N-DBPs with higher intensity clustered in the high O/C region than the HPO fraction of EfOM by both UV/chlorine and chlorination. Totally, 207 and 117 nitrogen-containing chlorinated formulae were recorded after UV/chlorine treatment of TPI and HPO, respectively. Precursor tracking found a greater number of DBPs were originated from raw EfOM through electrophilic substitution pathway rather than chlorine addition. Toxicity bioassays demonstrated that DBPs can trigger oxidative stress-induced DNA damage, while HPO fraction of EfOM dominated the induction of cytotoxicity. However, no correlation could be established between the diversity/abundance of N-DBPs and the level of DNA damage. A total of 22 DBPs with a significant rank correlation with DNA damage were identified, while C8 H6 O5 NCl was found as the N-DBP with the strongest correlation. The potential toxic chlorine-containing formula with the most abundant intensity was assigned to C5 HO3 Cl3 . This study suggests that the character and transformation of EfOM and associated toxicity is critical to evaluate the UV/chlorine process toward practical application. Graphical abstract: Image, graphical abstract